Annual Address to the Board of Governors, September 25, 1956 - Black, Eugene R. (World Bank, Washington, DC, 2019)
Eugene R. Black, President of the International Bank for Reconstruction and Development, mentioned lending done in Asia, which was more than in any other continent. He spoke about the non-lending activities of the Bank which also continued to expand during the year. He discussed the role of International Finance Corporation (IFC) which came into being in July. He concluded by saying that less developed countries hold large part of the key to the future of the world.